Cover Image. Issue 3 (27th February 2019) - Ekstedt, Sandra; Säfholm, Jesper; Georén, Susanna Kumlien; Cardell, Lars Olaf
Abstract : The cover image is based on the Original Article Dividing neutrophils in subsets reveals a significant role for activated neutrophils in the development of airway hyperreactivity by Sandra Ekstedt et al, https://doi.org/10.1111/cea.13311 .